Carbon dots based ratiometric fluorescent sensing platform for food safety. Issue 1 (2nd January 2022) - Han, Yong; Yang, Weixia; Luo, Xueli; He, Xie; Zhao, Haiping; Tang, Wenzhi; Yue, Tianli; Li, Zhonghong
Abstract: Food safety has become a major global concern and the rapid detection of food nutritional ingredients and contaminants has aroused much more attention. Nanomaterials-based fluorescent sensing holds great potential in designing highly sensitive and selective detection strategies for food safety analysis. Carbon dots (CDs) possess tremendous prospects in fluorescent sensing food ingredients and contaminants due to their superior properties of chemical and photostability, highly fluorescence with tunability, and no/low-toxicity. Numerous endeavors are demanded to contribute to overcoming the challenge of lower sensitivity and selectivity of the sensors interfered by various components in intricate food matrices to ensure food safety and human health. Nanohybrid CDs based ratiometric fluorescent sensing with self-calibration is regarded as an efficient strategy for the CDs based sensors for the specific recognition of target analyte in the food matrices. This work is devoted to reviewing the development of nanohybrid CDs based ratiometric fluorescent sensing platform and the perspectives of the platform for food safety. The applications of nanohybrid CDs in sensing are summarized and the sensing mechanisms are briefly discussed. Graphical Abstract: UF0001